2022
DOI: 10.3847/1538-4357/ac9b0f
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-mass Black Holes on the Run from Young Star Clusters

Abstract: The existence of black holes (BHs) with masses in the range between stellar remnants and supermassive BHs has only recently become unambiguously established. GW190521, a gravitational wave signal detected by the LIGO/Virgo Collaboration, provides the first direct evidence for the existence of such intermediate-mass BHs (IMBHs). This event sparked and continues to fuel discussion on the possible formation channels for such massive BHs. As the detection revealed, IMBHs can form via binary mergers of BHs in the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 122 publications
(149 reference statements)
0
0
0
Order By: Relevance
“…We now consider whether IMBHs could still be present in Milky Way GCs. Some previous studies ( 14 , 20 ) have found that IMBHs are ejected from their host clusters when they merge with another BH due to asymmetric gravitational wave emission (as discussed above). The recoil velocity from such a merger depends on the spin of both BHs and their masses.…”
Section: The Fate Of Imbhs In Gcsmentioning
confidence: 85%
See 3 more Smart Citations
“…We now consider whether IMBHs could still be present in Milky Way GCs. Some previous studies ( 14 , 20 ) have found that IMBHs are ejected from their host clusters when they merge with another BH due to asymmetric gravitational wave emission (as discussed above). The recoil velocity from such a merger depends on the spin of both BHs and their masses.…”
Section: The Fate Of Imbhs In Gcsmentioning
confidence: 85%
“…In the center of GCs, their most dense region, stars and BHs can collide and merge, potentially producing IMBHs ( 11 , 18 , 19 ). Numerical simulations have predicted that mergers of binary BHs can form IMBHs up to ~500 M ⨀ ( 12 14 ). However, BH mergers emit gravitational waves.…”
Section: Imbhs In Globular Clustersmentioning
confidence: 99%
See 2 more Smart Citations